Pan-asianism – Origin and Ideological Evolution in the Late XIX – Early XX Centuries - Yoneva, Elizabeth (Research Papers, 2021)
In view of the dynamic development of Asia in the late 19th and early 20th centuries in the context of expanding imperialism, the subject of genesis and ideological evolution of Pan-Asian concepts provokes special attention at research level. The paper explores the principal dimensions of the unfolding process of Pan-Asianism during this period. The author discusses the fundamental factors for its emergence in Japan and the directions for the manifestation of the „spillover effects” on other countries, which adopt these ideas, but also form their own directions in its development. The analysis showcases the main vectors of the expansion of Pan-Asianism, by applying a comparative perspective for its influence in the region.